Complications of hyaluronic acid fillers and their managements - Mohammed H. Abduljabbar; Mohammad A. Basendwh (Journal of Dermatology and Dermatologic Surgery, 2016)
Background: Injection of dermal fillers is one of the most commonly performed procedures in the cosmetic dermatology practice. As its usage is expanding, the possibility of complications will likely increase. Objective: To review and summarize the complications associated with hyaluronic acid injections, and to provide a guide to avoiding them and managing these complications if they do occur. Methods: A comprehensive PubMed and Google scholar electronic database search was performed (2005–July 2015). A total of fifty-five articles were selected and included. Results: Most of the complications associated with hyaluronic acid filler use are mild, transient and reversible. Serious complications due to vascular occlusion include cutaneous necrosis and blindness, which although rare can occur due to the compression of the vessel or direct intravascular injection. Conclusion: Injection related side effects are the most commonly seen, which are usually transient. Vascular occlusion is the most severe complication associated with hyaluronic acid filler injection. A thorough understanding of the facial vascular anatomy reduces the risk of vascular occlusion. Early identification of a vascular occlusion and a prompt intervention can significantly decrease the risk of long term sequelae. Guidelines to avoid, identify and manage different hyaluronic acid filler complications have been suggested.